Interface properties of MIS structures based on hetero-epitaxial graded-gap Hg1-xCdxTe with CdTe interlayer created in situ during MBE growth. (November 2017) - Voitsekhovskii, Alexander V.; Nesmelov, Sergey N.; Dzyadukh, Stanislav M.; Varavin, Vasily S.; Dvoretsky, Sergey A.; Mikhailov, Nikolay N.; Yakushev, Maksim V.; Sidorov, Georgy Yu.
Abstract: Heterostructures based on n-Hg1-x Cdx Te (x = 0.23–0.40) with near-surface graded-gap layers were grown by molecular beam epitaxy on Si (013) substrates. At 77 K, the admittance of the In/Al2 O3 /Hg1-x Cdx Te metal-insulator-semiconductor (MIS) structures with grown in situ CdTe intermediate layer and without such a layer was investigated. It has been established that MIS structures of In/Al2 O3 /Hg1-x Cdx Te with an interlayer of in situ grown CdTe are characterized by the electrical strength of the dielectric and the qualitative interface. The hysteresis of the capacitive characteristics is practically absent within a small range of variation in the bias voltage. The density of fast surface states at the minimum does not exceed 2.2 × 10 10  eV −1  cm −2 . MIS structures of In/Al2 O3 /Hg1-x Cdx Te without an intermediate layer of CdTe have significantly higher densities of fast and slow surface states, as well as lower values of the differential resistance of the space-charge region in the regime of strong inversion. Highligths: The In-Al2 O3 -hetero-epitaxial graded-gap HgCdTe structures were studied. Graded-gap HgCdTe grown by molecular-beam epitaxy on the Si (013) substrates. Impact of CdTe interlayer grown in situ on interface properties was studied. The densities of slow and fast interface states were studied. Growing the CdTe interlayer provides an excellent quality of the interface.